PDTM-23. CD57 DEFINES A NOVEL MARKER OF GLIOBLASTOMA STEM CELLS THAT DRIVES THE INVASION OF GBM. (5th November 2018) - Qi, Lin; Du, Yuchen; Kogiso, Mari; Braun, Frank; Lindsay, Holly; Zhang, Huiyuan; Zhao, Sibo; Injac, Sarah; Baxter, Patricia; Su, Jack; Mancini, Michael; Hampton, Oliver; et al.
Abstract: Glioblastoma multiforme (GBM) is the most lethal brain tumor. Diffuse invasion is one of the important biologic features that make GBM particularly difficult to treat. While existing studies on GBM invasion are primarily conducted in tumor core tissues from surgical resections, it is unclear whether infiltrative GBM cells would be more informative for studying their invasive nature, and little is known if and which cancer stem cell populations are driving GBM invasion. To address these issues, we utilized 6 patient tumor-derived orthotopic xenograft mouse models to isolate invasive GBM cells (GBM INV, infiltrating normal mouse brain parenchyma) and tumor core GBM cells (GBM TC ) and compared their biological features. Our result showed that the GBM INV cells have stronger neurosphere forming efficiency in vitro, more tumorigenic capacity in vivo, even some invasion-related genes also be detected to be changed in GBM INV cells. In the further study, gene profiling showed that CD57 is higher expressed in mostly GBM models and in patient tissues; CD57+ cells have stronger neurosphere formation ability with compared to CD57- cells; The survival time of mice injected with CD57+ cells decreases compared with mice with CD57- cells. Furthermore, CD57+ cells in GBM INV is higher expressed in PDOX invasive tumor cells than the expression of GBM TC cells; CD57+ cells in GBM INV cells are enriched (>2 folds) and have stronger neurosphere formation ability and more invasive with compared to GBM TC cells in mostly GBM models; The survival time of mice injected with GBM INV cells decreases compared with mice with GBM TC cells. We found that CD57+ cells expressed high levels of self-renewal genes (BMI1 and Nanog). In conclusion, we showed that invasive GBM cells were not biologically identical to the matched tumor core cells and identified CD57 as a novel stem cell marker that was associated with GBM infiltration.